Productivity and profitability of summer sunflower (Helianthus annuus L.) with integrated nutrient management: PRODUCTIVITY AND PROFITABILITY OF SUNFLOWER WITH INTEGRATED NUTRIENT MANAGEMENT - ANITA MAHAPATRA; B GOUDA; K RAMESH (Journal of Oilseeds Research, 2021)
A field experiment was conducted at College of Agriculture, Odisha University of Agriculture and Technology, Bhubaneswar on sandy loam soils during summer season of 2018-19 with an objective of evaluating nutrient management for enhancing sunflower productivity under eastern Indian conditions. The experiment was laid out in a randomized block design with three replications. There were twelve treatment combinations viz., 1. Control; 2. Recommended dose of fertilizers (RDF @ 60:80:60 kg N: P2O5 : K2O/ha); 3. RDF + S @ 40 kg/ha; 4. RDF + B @ 0.02%; 5. RDF + S @ 40 kg/ha + B @ 0.02%; 6. STBFR (60:100:60 kg N: P2O5 : K2O/ha + S @ 40 kg/ha + B @ 0.02%); 7. FYM @ 5 t/ha; 8. RDF + FYM @ 5 t/ha; 9. RDF + FYM @ 5 t/ha + S @ 40 kg/ha; 10. RDF + FYM @ 5 t/ha + B @ 0.02%; 11. RDF + FYM @ 5 t/ha + S @ 40 kg/ha + B @ 0.02%; 12. STBFR + FYM @ 5 t/ha. The results of the study indicated that integrated nutrient management exhibited significant effect on growth, seed and oil yield of sunflower. Application of STBFR + FYM @ 5 t/ha recorded significantly highest growth parameters, seed (2.59 t/ha) and oil yield (1114 kg/ha) of sunflower which remained at par with RDF + FYM @ 5 t/ha + S @ 40 kg/ha + B @ 0.02%. Highest gross (`141084/ha) and net returns (`85406/ha) were recorded with STBFR + FYM @ 5 t/ha.